STUDI ANALISIS HYBRID CONTRACT PADA PEMBIAYAAN IJARAH MUNTAHIA BI AL-TAMLIK DI PERBANKAN SYARIAH - Dimyati, Dimyati (TIJAROTANA : Jurnal Ekonomi dan Bisnis Syariah, 2020)
Hybrid contract in the financing of ijarah muntahia bi al-tamlik is to make two forms of contract, namely the lease agreement and the sale and purchase agreement into one. The concept of hybrid contract in the perspective of Islamic law is permissible. This is because some scholars have agreed on the ability to merge the two contracts. In the fiqh rules it has also been stated that the law of origin in all forms of mu'amalah is permissible unless there is a proposition that forbids it. In practice, the Syari'ah Financial Institution is inseparable from the decision of the National Syari'ah Council which in its fatwa mentioned the ability of a hybrid contract, namely in the fatwa of the National Syari'ah Council No.27/DSN-MUI/III/2002 about Ijarah Muntahia Bi Al-Tamlik.